2020
DOI: 10.1088/1742-6596/1462/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Study on Daily Activity Pattern of Captive Lion (Panthera leo) in Siantar Zoo, North Sumatra, Indonesia

Abstract: The present study investigated diurnal or daily activity patterns of an individual captive lion (Panthera leo) in Siantar Zoo, North Sumatra, Indonesia. Behavioral observations of 70 hours in 10-days observation were analyzed descriptively for common Felidae behaviors identified using a standardized Felidae ethogram. The methodology used was focal animal sampling with continuous sampling of data record or 5-minute sampling periods. We reported that the captive lion allocated the most time budgets in inactive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Lions slept most of the night, with sleep divided into few but long sleep phases. The results obtained on sleep behaviour are consistent with previous studies on captive lions [ 73 , 74 , 87 ]. In contrast to lions, cheetahs slept slightly less overall at night, with sleep divided into many short sleep phases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Lions slept most of the night, with sleep divided into few but long sleep phases. The results obtained on sleep behaviour are consistent with previous studies on captive lions [ 73 , 74 , 87 ]. In contrast to lions, cheetahs slept slightly less overall at night, with sleep divided into many short sleep phases.…”
Section: Discussionsupporting
confidence: 92%
“…Animals anticipated scheduled feeding times and got active around these assumed periods of time. Accordingly, previous research also showed that lions in zoos exhibit activity peaks during the day around feeding times [ 43 , 74 ]. Nevertheless, lions also showed a high percentage of resting behaviour during the day which is in line with observations on the diurnal resting behaviour of their wild conspecifics [ 3 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…the behavior of a lion was observed for ten days in Siantar Zoo, North Sumatra, Indonesia. Focal animal sampling was used for descriptive analysis of 70 hours of behavior observation [11]. Wagner et al observed the behavior of capuchin monkeys in the public Zoo of Vers-Duifen, Brazil, for 40 days to determine the frequency of stereotypical behavior and self-orientation and to analyze the effects on behavioral stability [12].…”
Section: Introductionmentioning
confidence: 99%